OP0219 Early onset of efficacy with apremilast monotherapy in biologic-naÏve patients with active psoriatic arthritis: a phase 3b, randomized, controlled trial. (15th June 2017) - Nash, P; Ohson, K; Walsh, J; Delev, N; Nguyen, D; Teng, L; Gomez-Reino, JJ; Aelion, JA
Abstract : Background: ACTIVE is the first apremilast (APR) trial to evaluate time to onset of efficacy beginning at Wk 2 in biologic-naïve psoriatic arthritis (PsA) patients (pts) who may have had exposure to 1 prior conventional DMARD. Objectives: Report the study results through Wk 52. Methods: Pts were randomized (1:1) to APR 30 mg BID or placebo (PBO). Pts were eligible for early escape (investigator discretion) at Wk 16. At Wk 24, all pts entered active treatment with APR. The primary endpoint was ACR20 response at Wk 16. Other assessments included changes in DAS-28 (CRP), SJC, TJC, HAQ-DI, morning stiffness duration/severity, and enthesitis, as measured by the Gladman Enthesitis Index (GEI; 0=no enthesitis, 6=all 6 sites active). Along with collection of safety data, tolerability adverse events (AEs) of diarrhea were further characterized. Results: 219 pts were randomized (APR: n=110; PBO: n=109); overall, 160/180 (88.9%) pts receiving APR completed Wk 52. Separation in the proportion of ACR20 responders to APR vs PBO was noted at Wk 2 (16.4% vs 6.4%; P =0.0252), the first post-baseline (BL) visit. Early onset of response to APR was observed across clinical assessments, with improvements in DAS-28 (CRP), SJC, HAQ-DI, enthesitis, and morning stiffness severity (Table). At Wk 16, significant ACR20 response rates were observed with APR vs PBO (38.2% vs 20.2%; P <0.005), with similar rates for the subset of pts with use of 1 prior non-biologic DMARD (39.2% vs 20.5%; P <0.05), which comprises 69% of study pts. Significant reductions in PsA disease activity/manifestations vs PBO were also demonstrated by changes in DAS-28 (CRP) ( P <0.0001), SJC, and HAQ-DI ( P =0.0229), and improvements in morning stiffness severity and GEI score ( P =0.0014). With continued APR exposure, the Wk 52 ACR20/ACR50/ACR70 response rates were 63.3%/32.4%/14.0%, and percent change in SJC was −74.5%. Among APR pts with BL enthesitis, 62.8% reached a GEI score of 0. Overall incidence of AEs in the PBO-controlled period was generally similar between APR and PBO. The most commonly reported AEs (≥5% of pts) with APR vs PBO were nasopharyngitis (8.3% vs 6.4%), nausea (8.3% vs 1.8%), headache (7.3% vs 3.7%), hypertension (6.4% vs 6.4%), and diarrhea (pt or investigator reported) (14.7% vs 11.0%); using a protocol-defined characterization of diarrhea (≥2 watery/liquid stools/day), overall incidence was lower for APR and PBO (11.0% and 8.3%). Serious AEs were lower with APR vs PBO (2.8% vs 4.6%). No opportunistic infections, reactivations of TB, or cases of marked depression were seen. In general, no increase was seen in AE incidence/severity with longer-term exposure to APR. Conclusions: In biologic-naïve pts treated with APR, onset of effect was observed starting at Wk 2 across PsA manifestations, including morning stiffness severity and enthesitis, with sustained improvements through Wk 52. AEs were consistent with those reported for other APR phase 3 PsA and psoriasis studies. Disclosure of Interest: P. Nash Grant/research support from: Celgene Corporation, K. Ohson Grant/research support from: Celgene Corporation, J. Walsh Consultant for: Celgene Corporation and Novartis, N. Delev Employee of: Celgene Corporation, D. Nguyen Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: BMS, Pfizer, Roche, Schering-Plough, UCB, J. Aelion Grant/research support from: AbbVie, Ardea Biosciences, AstraZeneca, BMS, Celgene Corporation, Centocor, Galápagos, Genentech, GlaxoSmithKline, Human Genome Sciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, Vertex Pharmaceuticals